Crystallization conditions and petrogenetic characterization of metaluminous to peraluminous calc-alkaline orogenic granitoids from mineralogical systematics: The case of the cambrian magmatism from the sierra de Guasayán (Argentina) - Zandomeni, Priscila Soledad (2021)
The Sierra de Guasayán (Eastern Sierras Pampeanas, Argentina) is formed by low to me-dium grade metamorphic rocks intruded by Cambrian metaluminous (La Soledad quartz-diorite), slightly peraluminous (Guasayán, El Escondido and El Martirizado granodiorite plutons), and strongly peraluminous (Alto Bello granodiorite) granitoids of the Pampean magmatic arc. Chemical compositions of amphibole, plagioclase, biotite, and titanite indicate that these granitoids were em-placed at low pressure (mostly <3 kbar) and temperature (<770 °C) under oxidizing conditions (QFM + 1 and QFM + 2), which are similar to the emplacement conditions reported for other granites of the Pampean magmatic arc. Mineral assemblages and whole-rock and mineral chemistry of the granitoids from the Sierra de Guasayán indicate an I-type affinity for the La Soledad quartz-diorite (amphibole, biotite, and titanite), S-type affinity for the Alto Bello granodiorite (biotite, muscovite, cordierite, and sillimanite), and a hybrid nature for the main Guasayán and El Escondido plutons (biotite, monazite, and magnetite). This hybrid nature is supported by the presence of abundant mafic microgranular enclaves and rapakivi texture and by published zircon Hf-isotope data (εHfi ranging from −4.76 to −0.12). This suggests, in turn, the involvement of hybridization in the genesis of these granitoids, which seems to be a common mechanism operating in the Pampean magmatic arc.